2020
DOI: 10.1111/pops.12655
|View full text |Cite
|
Sign up to set email alerts
|

Gender Attitudes and Public Opinion Towards Electoral Gender Quotas in Brazil

Abstract: Research on public opinion towards affirmative action shows that citizens often support the principle of equality while simultaneously rejecting policies that promote it in a pattern described as the “principle‐policy puzzle.” The scholarship also shows that ideology and prejudice towards the targeted group explain the puzzle with respect to racial affirmative action. In this article, we use unique survey questions included in the 2014 round of the AmericasBarometer in Brazil to show that citizens tend to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In this discourse, Marin appears as a norm breaker tarnishing her public image. This echoes Batista Pereira and Porto's (2020) study conducted in Brazil and Mexico, which found that female politicians face harsher accusations of corruption because they are expected to be honest and pure. The accusations of lying and corruption work as delegitimizing categorizations, while sexualized slurs are examples of shaming and dehumanizing categorization (Tileagă, 2007), both nevertheless aiming at reversing the image of ambitious and competent female leader into a calculating and cunning strategist who egoistically uses the media to promote her own interests and aspirations.…”
Section: Discussionmentioning
confidence: 62%
“…In this discourse, Marin appears as a norm breaker tarnishing her public image. This echoes Batista Pereira and Porto's (2020) study conducted in Brazil and Mexico, which found that female politicians face harsher accusations of corruption because they are expected to be honest and pure. The accusations of lying and corruption work as delegitimizing categorizations, while sexualized slurs are examples of shaming and dehumanizing categorization (Tileagă, 2007), both nevertheless aiming at reversing the image of ambitious and competent female leader into a calculating and cunning strategist who egoistically uses the media to promote her own interests and aspirations.…”
Section: Discussionmentioning
confidence: 62%
“…There is also evidence that individuals with negative stereotypes of female leaders are more likely to oppose legislative gender quotas than those with neutral or favorable views (Smith, Warming, and Hennings 2017). Recent research extends this literature by showing that individuals with benevolent sexism tend to support gender quotas while rejecting the principle of gender equality (Batista Pereira and Porto 2020; Beauregard and Sheppard 2021). Additionally, Barnes and Córdova (2016) demonstrate that citizens who favor active government involvement or those exhibiting high levels of trust in government support legislative gender quotas.…”
Section: Determinants Of Attitudes Toward Gender Equality Policiesmentioning
confidence: 84%
“…Public opinion also matters even after a new policy is adopted, as public opposition can incur backlash against candidates of underrepresented groups (Clayton 2015). Recognizing this fact, scholars have investigated the individual‐level determinants of attitudes toward gender quotas emphasizing political values and views on gender norms (Barnes and Córdova 2016; Batista Pereira and Porto 2020). We make an important departure from this previous work by examining the effects of economic anxiety independent of norms and values on public support for this policy.…”
mentioning
confidence: 99%
“…Similarly to studies on other countries, research on Brazil indicates that voters positively stereotype women politicians in traditionally gendered ways, thinking of them as more pure and morally superior than men (Batista Pereira and Porto, 2020;. The health crisis also likely increased the value of traits traditionally associated with women (Johnson and Williams, 2020): Not only is healthcare a "feminine" policy area (Bauer et al, 2020), but women politicians are also expected to be more caring towards the vulnerable and sick (Johnson and Williams, 2020) and more risk-averse (Palmer and Peterson, 2020)-and, thus, more compliant towards mask-wearing and social distancing rules.…”
Section: Gendering Stigmatized Practices Candidate Viability and Punishmentmentioning
confidence: 91%
“…Positive stereotypes seem to, at least in part, explain voters' pro-women bias and desire for more women in politics (Batista Pereira and Porto, 2020). As previous work has shown, women politicians are often characterized as being more honest and ethical (Brooks, 2013;Dolan, 2014;Schneider and Bos, 2014) and less likely to engage in moral transgressions than men (Barnes and Beaulieu, 2014;Z ̇emojtel-Piotrowska et al, 2017).…”
Section: Gendering Stigmatized Practices Candidate Viability and Punishmentmentioning
confidence: 97%